The Word Gat‘a in the Armenian Language - Hasmik Hmayakyan (Banber Arevelagitut'yan Instituti)
Գաթայ gat‘ay (pronounced gat‘a in the modern Eastern Armenian) is an ancient traditional festive cake, which was baked during various Armenian celebrations. Its baking process was sometimes itself accompanied by special traditions. However, it should be noted that the word gat‘a used today, which means ‘cake in the form of bałarĵ (traditional Armenian festive bread) containing abundant fat and sugar’is not found in ancient Armenian sources. Gat‘ay is met for the first time in Vardan Aygektsi’s fable ‘The Pig and Gata’ in the following passage: «Ասաց 'ի առակաց, թէ խոզն գաթայ մի գտեալ ուտէր. նայ խորիսն 'ի վայր կու թափէր եւ վասն պարանոցին միաբերութեան զի վիզն ոչ կարէր շեղել. որ զգլուխն 'ի վեր կալնուր. յայնժամ բերընցիք'ի վեր անկեալ եւ ետես արեգակն. զի խոզն զբոլորութիւն արեգականն աչօք չէ տեսեալ։ Եւ այնժամ ասաց, թէ զոր չէի կերեր, կերայ եւ զինչ չէի տեսեալ, տեսայ. զի այլ ոչ գաթայ էր կերեր եւ ոչ արեգակն տեսեր։ "It is said in a fable that a pig was eating gat‘ay it had found, the pig was dropping xoriz as it was not able to move its neck as it was attached to its head. As soon as it raised its head in order to raise its mouth it saw the sun. The pig had never seen the entire sun disk. And then it said I ate what I have never eaten and I saw what I have never seen. If it had not eaten gat‘ay, it would have never seen the sun ’. The word գաթայ (gat‘ay) is encountered often in Middle Armenian including in medieval lyric poetry․